Seismic vulnerability assessment and retrofitting of historic masonry building of Malek Timche in Tabriz Grand Bazaar - Aghabeigi, Pouya; Farahmand-Tabar, Salar (Engineering structures, 2021)
[Display omitted] •Finite-Element model of Malek Timcha is developed considering material experiments.•Dynamic properties of the structure are obtained and seismic analysis is carried out.•Possible failure mechanisms are obtained based on stress contours achieved using simplified kinematic method.•Retrofitting method is proposed that enhance the behavior of Malek Timcha under seismic load. Tabriz Bazaar is the first Bazaar in the world that was registered in the world heritage list of the UNESCO in August 2010. Malek Timche is one of the important and beautiful parts of Tabriz Bazaar. The objective of this research is to assess the seismic vulnerability, structural behavior and failure mechanisms of this historic building, and to propose an appropriate method for retrofitting and improving the seismic performance. The subject is studied in four main steps. To determine the mechanical properties of constructional materials, three-point bending test and compression test are carried out initially. Then, a three-dimensional model of the Malek Timche is established using finite element method, and the static, modal, and dynamic analysis are performed. In the third step, 16 possible failure mechanisms are obtained based on the stress contours achieved from dynamic analyses using the simplified kinematic method based on the Italian code, OPCM 3431. Finally, by using the results of the structural analysis, walls and domes of the structure are strengthened by reinforcements and FRP composites, respectively.